Wild earth - Simon, Seymour (New York : Scholastic, 2009)
Acclaimed author Seymour Simon answers these questions and many more about our planet. You'll learn about avalanches, earthquakes, volcanic bombs, tsunami waves, and more! With incredible photos and fascinating facts, this is the perfect answer to all your questions about our wild and wonderful earth.